Implementasi Pendidikan Nilai-Nilai KeIslaman dalam Konteks Kewirausahaan: Studi pada kinerja alumni pesantren Almushlih Karawang yang berwirausaha - Latif, Abdul; Sakum; Mamun, Sukron; Achmad, Yudianto; Ainulyaqin, M.H (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to explore the impact of Islamic values education on the business performance of pesantren alumni, as well as to understand the impact of Islamic values on the performance of pesantren alumni who are entrepreneurs. This study used a qualitative approach to gain an in-depth understanding of the implementation of Islamic values education in the business context. Data collection used the interview method. Researchers conducted in-depth interviews with several pesantren alumni who are currently entrepreneurs. The education pattern at Almushlih Islamic Boarding School in Karawang Regency applies a curriculum based on the understanding of Ahlus Sunnah wal Jamaah and the use of classical books in the fields of tawhid, Sufism, and fiqh. This pesantren has succeeded in instilling strong Islamic values in its students. Traits such as tawakal, qanaah, honesty, trustworthiness, patience, istiqamah, wara, humility, and compassion, which are taught through these sciences, have proven to be important elements in shaping the character of successful entrepreneurs. These values help entrepreneurs in facing challenges, making wise and ethical decisions, and building strong relationships with all stakeholders. As a result, pesantren alumni not only achieve financial success but are also able to create a positive impact on their community and environment.